Quantitative Logic and Soft Computing 2016 : Proceedings of the 4th International Conference on Quantitative Logic and Soft Computing (QLSC2016) held at Hangzhou, China, 14-17 October, 2016 /: Proceedings of the 4th International Conference on Quantitative Logic and Soft Computing (QLSC2016) held at Hangzhou, China, 14-17 October, 2016. (2017) - Unknown
No abstract available